2021
DOI: 10.1097/brs.0000000000004064
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Implications of Concurrent Complications Following Adult Spinal Deformity Corrective Surgery

Abstract: Study Design. Retrospective review. Objective. Identify co-occurring perioperative complications and associated predictors in a population of patients undergoing surgery for adult spinal deformity (ASD). Summary of Background Data. Few studies have investigated the development of multiple, co-occurring complications following ASD-corrective surgery. Preoperative risk stratification may benefit from identification of factors associated with multiple, co-occurring complications. Methods. Elective ASD patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
(56 reference statements)
1
6
0
Order By: Relevance
“…Longer OR time was also associated with an increased rate of postoperative minor complications ( P =0.001), but was not related to the rate of major complications. These results are supported by multiple previous studies 1,3,24–31 . Lee et al 25 found that OR time was the most correlated to morbidity with an odds ratio of 3.5 ( P <0.0001).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Longer OR time was also associated with an increased rate of postoperative minor complications ( P =0.001), but was not related to the rate of major complications. These results are supported by multiple previous studies 1,3,24–31 . Lee et al 25 found that OR time was the most correlated to morbidity with an odds ratio of 3.5 ( P <0.0001).…”
Section: Discussionsupporting
confidence: 87%
“…These results are supported by multiple previous studies. 1,3,[24][25][26][27][28][29][30][31] Lee et al 25 found that OR time was the most correlated to morbidity with an odds ratio of 3.5 (P < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Complications that cluster can lead to increased morbidity and may have a significant impact on hospital length of stay. Bortz et al [ 5 ] demonstrated a 6% rate of concurrent complications in adults undergoing correction for adult spinal deformity, but there have been no studies examining co-occurring or concurrent post-fusion complications among pediatric patients with neuromuscular scoliosis.…”
Section: Introductionmentioning
confidence: 99%
“…17 Similarly, these procedures have also demonstrated high rates of complications both perioperatively and in the long term, with elevated rates of complications and revision. 18 Therefore, surgeons have been investigating new techniques to mitigate the elevated risk profile of these invasive surgeries while still achieving the same clinical and radiographic outcomes. A particularly attractive technique that has gained popularity as of late is the single-position approach to circumferential fusion.…”
mentioning
confidence: 99%
“…Yet, despite the added benefits of this strategy, some patients have more focal deformity and degeneration in the thoracolumbar spine, which may only require the fusion of one to three levels to address the root of their symptomatology 17 . Similarly, these procedures have also demonstrated high rates of complications both perioperatively and in the long term, with elevated rates of complications and revision 18 . Therefore, surgeons have been investigating new techniques to mitigate the elevated risk profile of these invasive surgeries while still achieving the same clinical and radiographic outcomes.…”
mentioning
confidence: 99%